Políticas públicas em educação e o ideário neoliberal e pós-moderno: a ciência geográfica como instrumento crítico de análise da conjuntura contemporânea - Lopes, Paulo Eduardo Vasconcelos de Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
In this work, we presents an analysis of Neoliberal and Postmodern system in education public politics from the social reorganization attempted in Brazil State reform in 90´s years and the geographic science as a critic instrument of the analysis of contemporaneous conjuncture. This study is organized in six chapters. In the first chapter, the worry happen in the presentation of an historical construction of the geographical thought, put in evidence its critic character in front of the State performance. In the second, we analysed the articulation of transformations undertake in the capitalism in the last decades that has reflection in the society organization as a whole. Thys, we analyse the productive process under the logician Taulororistic/Fordistic, and after that, under the logician of Toytism, introducing some politic and economic projects of the flexible accumulation that generate the neoliberalism. In the third, we make an analyse of the Postmodern ideology as a conjoint of theorist-methodological principles of ideologic character consolidated on the Neoliberal State projecture, searching its origin ant its preachment about a new (i)rationality. In the fourth, we analysed the Brazilian State reformulation emanate from the influence of Neoliberal and Postmodern ideate, to put in evidence the social reorganization undertake under a perspective of the marketing efficiency required, preconized by many multilateral international organs and the influence of this new rationality in Brazilian public politics in education. In the fifth, we present the methodologic universe, since we choose to work with positive statement that rendered favorable a better progress in the analyse the discourse of the professors. In the sixth, we undertake a discussion about the geographic science and the analyse of the scholar practice in front of Neoliberal and Postmodern ideate by meanst of the discourse make by educators subjects of this research ...

Neste trabalho, apresentamos uma análise da penetração do ideário neoliberal e pós-moderno nas políticas públicas em educação a partir da reengenharia social empreendida na reforma do Estado no Brasil nos anos de 1990 e a ciência geográfica como instrumento crítico de análise da conjuntura contemporânea. O estudo está organizado em seis capítulos. No primeiro capítulo, a preocupação incide em apresentar a construção histórica do pensamento geográfico, evidenciando seu caráter crítico frente à atuação do Estado. No segundo capítulo, buscamos analisar a articulação entre as transformações empreendidas no capitalismo nas últimas décadas que repercutem na organização da sociedade como um todo. Desse modo, analisamos o processo produtivo sob a lógica Taylorista/Fordista e, em seguida, sob a lógica do Toyotismo, apresentando alguns pressupostos políticos e econômicos da acumulação flexível que engendram o Neoliberalismo. No terceiro capítulo, fizemos uma análise da ideologia Pós-moderna como um conjunto de princípios teórico-metodológicos de caráter ideológico que se fortalece no bojo do Estado Neoliberal, examinando sua origem e sua pregação acerca de uma nova (i)racionalidade. No quarto capítulo, analisamos a reforma do Estado brasileiro a partir da influência do ideário Neoliberal e Pós-moderno, evidenciando a reengenharia social empreendida sob a perspectiva da eficiência mercadológica exigida, preconizada por diversos órgãos internacionais multilaterais e a influência desta nova racionalidade nas políticas públicas educacionais brasileiras. No quinto capítulo, apresentamos o universo metodológico, uma vez que optamos por trabalhar com assertivas que propiciam um melhor desenvolvimento na análise do discurso do professores. No sexto capítulo empreendemos uma discussão sobre a ciência geográfica e a análise da prática escolar ...
Keywords: Educação; Educação e Estado; Neoliberalismo; Pós-modernismo; Geografia politica; Education